Incorporating carbon sink of harvested wood products into ecological footprint accounting: model and case study. Issue 1 (16th December 2020) - Gao, Wei; Cheng, Guowei; Liu, Chang'e
ABSTRACT: Ecological footprint (EF) accounting system is widely used in assessing environmental sustainability at various spatial scales. To improve the EF performance, a new EF calculation framework was established in this study, in which HWP is considered as carbon sinks and the model was then applied to the Yangtze River basin of China. Results showed that (1) carbon sink in the basin is about 2.99 Tg per year and it varies substantially across subbasins, which has a nonlinear relationship with net primary productivity; (2) available biocapacity calculated in the whole basin increases from 0.5068 to 0.5759 national ha (nha) per capita when incorporating the carbon sinks. In a few subbasins, the added biocapacity is even larger than the biocapacity estimated from the conventional approach; (3) the EF of the basin is 5.598 nha per capita and it is much larger than its biological carrying capacity (BC), indicating that ecological deficit is ubiquitous across the basin. If carbon sinks are considered, the ecological deficit would decrease by 3.2–14.3% for different regions in the basin. It is necessary to incorporate HWP and other potential terrestrial carbon sinks in the EF accounting, and more efforts are needed in improving carbon sink accuracy.